Left ventricular assist device and transcatheter edge-to-edge mitral valve repair in advanced heart failure: allies or enemies? - Valente, S.; Sciaccaluga, C.; Sorini Dini, C.; Righini, F. M.; Cameli, M.; Bernazzali, S.; Maccherini, M.; Tarzia, V.; Gerosa, G. (Frontiers in Cardiovascular Medicine, 2024)
The implantation of left ventricular assist devices (LVADs) has been increasing, with good long-term results, in parallel with a growing population with advanced heart failure (HF). However, in some European countries, LVADs are still underused, with one of the main issues being the patient's late referral. On the contrary, the use of transcatheter edge-to-edge mitral valve repair (TEER) has exponentially increased over the past decade, expanding its potential use even in patients on the heart transplantation waiting list. Even though the study populations of the main trials that investigated the prognostic impact of LVAD and TEER are different, in clinical practice a clear distinction might not be so clear. Therefore, patients with refractory HF symptoms and significant mitral regurgitation should be thoroughly evaluated through a multidisciplinary Heart Team meeting with both an advanced HF specialist and interventional cardiologist, to avoid futile procedures and to define the optimal timing for advanced HF therapies, when they are indicated. We analyzed the main available studies and registries on both TEERs and LVADs and we compared their populations and outcomes, to provide the current evidence on the use of LVAD and TEER in the HF population, especially in the light of the recently released 5-year follow-up results, giving some insights on the Italian situation, and finally to stress the importance of a solid HF network between hospitals, aiming for advanced HF patients’ timely referral for LVAD or heart transplants.